Makna Busana dan Penokohan Wajir dalam Teater Tradisional Mamanda - Khairunnida Khairunnida (Pelataran Seni, 2016)
AbstractResearch descriptive-qualitative manifold trying to make sense of fashion and the characteristics of the characterizations of the characters in the traditional theater Mamanda, Wajir. Data were obtained through observation, interviews and documentation. At the show Mamanda, Wajir is a character that has a very important role. Theater semiotic analysis is used as a method in conclusion. From the analysis, it was found that the difference between the figures Wajir with another character on the show Mamanda is on the clothing she was wearing. Wajir Clothing is known to contain the influence of Chinese culture and Arabic. From the characteristics and form of clothing Wajir, it can be concluded that the clothing and characterizations Wajir teach the values of religious and moral education.Keywords: mamanda, wajir, fashion, character, traditional theater